(untitled) (Gaceta Técnica, 2017)
The construction industry is considered as one of the industries with lower yields, frequent delays and reprogramming. Due to this and to avoid losses of time, costs and inconveniences in the execution, the virtual construction is used, that allows to analyze previously the constructive sequences and the possible interferences between the different activities through a real time scenario according to the programmed schedule . This article shows the implementation of BIM technology in a modular housing development in Venezuela. Four 4D simulations were carried out, two initially due to the original planning and its timely improvement, and two subsequent corresponding to reprogramming due to actual delays in execution due to lack of concrete supply. The main results were: problems of programming logic, interferences between activities, unreal sequences, among others in the first models. As for the models of the reprogramming gave resulting times very similar to reality; this means that the models work both in ideal situations and in situations of uncertainty. Building information modeling solutions introduce a new way of working, based on the creation and use of coherent and coordinated information, which allows for faster decision making, better documentation and the possibility of predicting the drawbacks even before the work began.